2020
DOI: 10.3791/60485
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Culture of Human Mature Adipocytes Using Membrane Mature Adipocyte Aggregate Cultures (MAAC)

Abstract: White adipose tissue (WAT) dysregulation plays a central role in development of insulin resistance and type 2 diabetes (T2D). To develop new treatments for T2D, more physiologically relevant in vitro adipocyte models are required. This study describes a new technique to isolate and culture mature human adipocytes. This method is entitled MAAC (membrane mature adipocyte aggregate culture), and compared to other adipocyte in vitro models, MAAC possesses an adipogenic gene signature that is the closest to freshly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Indeed, the 2D adipocyte model requires additional growth factors to drive differentiation, which may result in a variability in differentiation efficiency and cell maturity. Thus, 2D-cultured adipocytes are smaller in size and lack a unilocular lipid droplet as compared to the 3D-cultured cells ( Alexandersson et al., 2020 ; Harms et al., 2019 ). These differences may significantly affect the cell’s biology, rendering 2D-cultured adipocytes less responsive to SPM treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, the 2D adipocyte model requires additional growth factors to drive differentiation, which may result in a variability in differentiation efficiency and cell maturity. Thus, 2D-cultured adipocytes are smaller in size and lack a unilocular lipid droplet as compared to the 3D-cultured cells ( Alexandersson et al., 2020 ; Harms et al., 2019 ). These differences may significantly affect the cell’s biology, rendering 2D-cultured adipocytes less responsive to SPM treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile, the adipose stroma vascular fraction (SVF) was pelleted through centrifugation (200 g , 7 min at room temperature) and used for experiments as described below. Additionally, the mature floating adipocytes were washed three times in KRHB wash buffer (120 mM NaCl, 4.7 mM KCl, 1.2 mM KH 2 PO 4 , 1.2 mM MgSO 4 · 7 H 2 O, 2.5 mM CaCl 2 · 2 H 2 O, 25 mM HEPES, 2 mM glucose, 2% BSA, pH 7.4) using a separation funnel (VWR) to ensure removal of any remaining collagenase, leaving the mature adipocytes to be cultured as described in the MAAC procedure below ( Alexandersson et al., 2020 ; Harms et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Brite adipocytes are, however, largely absent in the WAT of most adult humans under normal conditions, possibly due to living in thermoneutral conditions. In human subcutaneous WAT, distinct precursor pools with brite adipogenic potential have been identified [51–53], and we have recently shown that mature adipocytes also have the ability to transdifferentiate into brite cells in vitro [19,54,55]. Thus, browning of WAT may be of a similar nature in humans as it has been shown to occur in rodents, with brite cells emerging from both differentiation of precursor cells and transdifferentiation from existing white adipocytes (Fig.…”
Section: The Phenotypic Versatility Of Mammalian Adipose Tissuementioning
confidence: 93%
“…Mature adipocytes were isolated and cultured as previously described by Alexandersson et al [ 23 ] with modifications. Briefly, 50 g of fat was minced, and the resulting homogenous mixture was added to 250 mL of digestion buffer (TC 199) containing 4.2 mM NaHCO 3 , 15 mM bovine serum albumin (BSA), 5.5 mM D-glucose, 1% penicillin–streptomycin, collagenase type I (1 mg/mL), 1.6 mM DNase, and 2.5 mM trypsin inhibitor.…”
Section: Methodsmentioning
confidence: 99%